2021
DOI: 10.1097/cad.0000000000001145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GADD45G on the radioresistance of nasopharyngeal carcinoma cells

Abstract: The development of radioresistance by nasopharyngeal carcinoma (NPC) cells almost always results in tumor recurrence and metastasis, making clinical treatment of the disease difficult. In this study, the mechanism of radioresistance in NPC cells was investigated. First, a gene array and quantitative reverse-transcription-PCR assays were used to screen for genes exhibiting significantly altered expression in the DNA damage signaling pathway. Based on those results, GADD45G was further studied in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Recent clinical researches have shown that GADD45g expression is elevated in various CMs and may serve as a biomarker of myocardial injury 43 . In addition, GADD45g plays a role in regulating proliferation in different cancers 44 . It was found that Gadd45 protein interacts with cyclin-dependent kinase 1 (Cdk1), which is a strong inhibitor of Cdk1-cyclin B1 activity, both in vivo and in vitro 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical researches have shown that GADD45g expression is elevated in various CMs and may serve as a biomarker of myocardial injury 43 . In addition, GADD45g plays a role in regulating proliferation in different cancers 44 . It was found that Gadd45 protein interacts with cyclin-dependent kinase 1 (Cdk1), which is a strong inhibitor of Cdk1-cyclin B1 activity, both in vivo and in vitro 45 .…”
Section: Discussionmentioning
confidence: 99%
“…GADD45g gene, localized on chromosome 9q22.1-q22.2, is an evolutionarily conserved small molecule encoding an 18-kDa protein that plays a critical role in cell cycle regulation, apoptosis, and DNA damage repair 5,6 . Some studies have demonstrated that the expression of GADD45g is downregulated in breast cancer 7 , esophageal squamous carcinoma 8 , and nasopharyngeal carcinoma 9 , and the mechanism involves changes in promoter methylation or post-transcriptional modi cations 10 . In addition, GADD45g overexpression signi cantly decreases tumor cell proliferation, methylation, or post-transcriptional modi cation 10 .…”
Section: Introductionmentioning
confidence: 99%